Accounting for family and business overlaps. Issue 2 (9th December 2019) - Quinn, Martin; Hiebl, Martin; Mazzotta, Romilda; Veltri, Stefania
Abstract : Purpose: This paper aims to draw on a family business perspective to explore the historic accounting records of an Italian liquorice juice business. The applicability of the three-circle model of family business systems to such an historic context is examined. Design/methodology/approach: Using archival records, the Cassa accounting book of the business is studied. Its transactions are examined to distinguish family and business items over the period from 1875 to 1920. Findings: Through an analysis of the accounting records, the family, ownership and business systems are shown to overlap more than typically expected in a contemporary setting. Originality/value: Contemporary literature suggests the three-circle model of a family business is relatively static, but it has not been applied to an historic context. This study suggests that the model can be applied in historic studies, but it is not static over time with its elements needing refinement.